Highly Stretchable Sound‐in‐Display Electronics Based on Strain‐Insensitive Metallic Nanonetworks. Issue 1 (23rd November 2020) - Cho, Seungse; Kang, Dong‐hee; Lee, Hyejin; Kim, Minsoo P.; Kang, Saewon; Shanker, Ravi; Ko, Hyunhyub
Abstract: The growing importance of human–machine interfaces and the rapid expansion of the internet of things (IoT) have inspired the integration of displays with sound generation systems to afford stretchable sound‐in‐display devices and thus establish human‐to‐machine connections via auditory system visualization. Herein, the synchronized generation of sound and color is demonstrated for a stretchable sound‐in‐display device with electrodes of strain‐insensitive silver nanowires (AgNWs) and emissive layers of field‐induced inorganic electroluminescent (EL) phosphors. In this device, EL phosphors embedded in a dielectric elastomer actuator (DEA) emit light under alternating‐current bias, while audible sound waves are simultaneously generated via DEA actuation along with input sound signals. The electroluminescence and sound‐generation performances of the fabricated device are highly robust and reliable, being insensitive to stretch‐release cycling because of the presence of the AgNW stretchable electrodes. The presented principle of integrating light emission and acoustic systems in a single stretchable device can be further expanded to realize sound‐in‐display electronics for IoT and human–machine interface applications. Abstract : A stretchable sound‐in‐display with electrodes of strain‐insensitive silver nanowires and emissive layers of field‐induced inorganic electroluminescent (EL) phosphors are proposed for generation of synchronized acoustic and visual information. The loudspeaker simultaneously emits light by the EL and generates sound by the vibration of the dielectric elastomer actuator under the same bias, allowing the synesthetic perception of both color and sound.